Pemetaan Budaya Dan Tanah Adat Marind Di Kampung Ivimaad Distrik Kurik Kabupaten Merauke - Hesty Tambajong; Izak Wayangkau; Paul Adryani Moento; Hubertus Oja (Yayasan Perguruan Kampus, 2024)
Apart from culture, every community has ancestral heritage in the form of customary land or what is called customary land of indigenous communities based on the origins of their ancestors based on areas that have been determined by the indigenous communities themselves. This is the case with the traditional community of Ivimahad village in the Kurik district, Merauke district. The Marind community in this village has their own customary area based on customary land mapping that has been regulated by the ancestors of each clan. Along with population development and growth, the life of indigenous communities began to shift in perspective. To improve this, the government and indigenous communities should work together to legally determine the cultural heritage of each indigenous community, starting from mapping clans according to their descendants to the cultural legacies left behind. This service is carried out with the aim of providing input to the wider community and the government regarding cultural and customary land mapping in Ivimahad village, considering that there are many problems that have occurred regarding cultural inheritance rights as well as providing understanding to parties regarding the mapping of customary rights that are appropriate to the territory of each traditional clan.